2012
DOI: 10.1016/j.autcon.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Construction safety and digital design: A review

Abstract: As digital technologies become widely used in designing buildings and infrastructure, questions arise about their impacts on construction safety. This review explores relationships between construction safety and digital design practices with the aim of fostering and directing further research. It surveys state-of-the-art research on databases, virtual reality, geographic information systems, 4D CAD, building information modeling and sensing technologies, finding various digital tools for addressing safety iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
121
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(145 citation statements)
references
References 58 publications
0
121
0
4
Order By: Relevance
“…Occupational injuries from the construction field are a global public health issue, whereas the construction sector is a hazardous industry in which occupational accidents occur most frequently around the world [1]. Usnar and Sut [2] confirmed that from 2000 to 2005 in Turkey, occupational fatalities of the construction industry were much higher than in any other industry.…”
Section: Introductionmentioning
confidence: 57%
“…Occupational injuries from the construction field are a global public health issue, whereas the construction sector is a hazardous industry in which occupational accidents occur most frequently around the world [1]. Usnar and Sut [2] confirmed that from 2000 to 2005 in Turkey, occupational fatalities of the construction industry were much higher than in any other industry.…”
Section: Introductionmentioning
confidence: 57%
“…In the area of construction safety, the applications and researches on BIM has also been widely recognized, focusing on the planning and design phases to improve safety during construction by connecting construction safety issues to construction planning [4], [5], and [6]. BIM-based modelling and 4D simulation allow design engineers to exercise various design alternatives that best address safety issues, as well as determining whether any proposed design change is integrated into final construction plans.…”
Section: Bim and Visualization Of Construction Processmentioning
confidence: 99%
“…Thus, occupational accidents are a serious global public health issue [1]. The industrial occupational accidents are influenced by a wide range of factors such as personal, business, and social variables.…”
Section: Introductionmentioning
confidence: 99%